Doğu Akdeniz'de münhasır ekonomik bölge uyuşmazlığı - Tekin, Fatma Betül (My University, 2019)
Dünyada sanayileşmenin beraberinde getirdiği yoğun tüketim enerji kaynağı arayışlarını arttırmış ve son olarak bu arayış denizlerdeki petrol ve gaz yataklarına yönelmiştir. Bunun üzerine insanlığın ortak malı kabul edilen denizler üzerindeki hâkimiyet mücadelesi de hız kazanmıştır. Denizlere ilişkin kullanım yalnızca kıyılara yakın olan kesimlerle sınırlı kalmamış, günümüzde insanlığın ortak malı sayılan okyanusların kullanımı da yaygınlaşmış ve bu hususta pek çok uluslararası sözleşme yapılmıştır. Bu kapsamda, Doğu Akdeniz’de keşfedilen zengin hidrokarbon kaynakları bölgede denizler üzerindeki egemenliğin önemini arttırmıştır. Doğu Akdeniz’e kıyısı olan devletlerin deniz alanlarını ikili anlaşmalarla paylaşması ve bu anlaşmalarda Türk kıta sahanlığını ihlal etmeleri üzerine Türkiye’de Doğu Akdeniz deniz yetki alanlarına verilen önem artmıştır. Önemle belirtilmesi gerekir ki Kıbrıs, Meis, Karaada ve Fener gibi pek çok ada, Doğu Akdeniz’deki deniz yetki alanlarının sınırlandırılmasında kilit öneme sahiptir. Sahildar devletlerin bu yarı kapalı deniz üzerindeki egemenlik iddialarının deniz yetki alanları hususunda uyuşmazlık yarattığı aşikardır. Bu nedenle, bu çalışmanın amacı, Doğu Akdeniz’de deniz yetki alanlarının paylaşımı konusunda yaşanan uyuşmazlıkları ve sahildar devletlerin bu konudaki uygulamalarını inceleyerek Türkiye’nin Doğu Akdeniz özelinde uluslararası hukuka göre ileri sürebileceği olası argümanları ortaya koymaktır.

The intensive consumption stemmed from industrialization in the world has increased the search for energy sources and in the recent years this search has been directed towards the oil and gas deposits in the seas. Thereupon, the battle for dominance over the seas, which are accepted as common property of mankind, has also accelerated. The exploitation of the seas is not limited with the areas closed to shores; today, the oceans that are considered as the common property of mankind have been exploited as well and in this regard many international conventions have been introduced. In this context, the rich hydrocarbon resources discovered in the Eastern Mediterranean have increased the importance of sovereignty over the seas in the region. Due to the division of maritime boundaries through the bilateral agreements between the states located within the Eastern Mediterranean coasts and violations on Turkey’s rights arising from continental shelf, Turkey has given greater importance to maritime boundaries issue in the Eastern Mediterranean. It is crucial to state that many islands such as Cyprus, Meis, Rho, (Karaada) and Hypsili (Fener) located in the Eastern Mediterranean have vital importance on the issue of delimitation of maritime boundaries. It is explicit that the sovereignty claims of the coastal states over this semi-closed sea create some disputes with regard to maritime boundaries. Therefore, the aim of this study is to present the possible legal arguments, which could be alleged by Turkey under international law, by examining the dispute regarding the delimitation of maritime boundaries in the Eastern Mediterranean and practices conducted by the coastal states.
Keywords: (Karaada) and Hypsili (Fener) located in the Eastern Mediterranean have vital importance on the issue of delimitation of maritime boundaries; by examining the dispute regarding the delimitation of maritime boundaries in the Eastern Mediterranean and practices conducted by the coastal states; deniz yetki alanları; deniz yetki alanlarının sınırlandırılması The intensive consumption stemmed from industrialization in the world has increased the search for energy sources and in the recent years this search has been directed towards the oil and gas deposits in the seas; Doğu Akdeniz uyuşmazlığı; Due to the division of maritime boundaries through the bilateral agreements between the states located within the Eastern Mediterranean coasts and violations on Turkey’s rights arising from continental shelf; has also accelerated; Hukuk; In this context; It is crucial to state that many islands such as Cyprus; It is explicit that the sovereignty claims of the coastal states over this semi-closed sea create some disputes with regard to maritime boundaries; Kamu hukuku; kıta sahanlığı; Law; Meis; Münhasır ekonomik bölge; Public law; Rho; the aim of this study is to present the possible legal arguments; the battle for dominance over the seas; The exploitation of the seas is not limited with the areas closed to shores; the oceans that are considered as the common property of mankind have been exploited as well and in this regard many international conventions have been introduced; the rich hydrocarbon resources discovered in the Eastern Mediterranean have increased the importance of sovereignty over the seas in the region; Therefore; Thereupon; today; Turkey has given greater importance to maritime boundaries issue in the Eastern Mediterranean; which are accepted as common property of mankind; which could be alleged by Turkey under international law